PRODUCTIVE WAQF MANAGEMENT VIEWED FROM THE MAQASID SYARIAH ASPECT AT THE UMI MAKASSAR WAQF FOUNDATION - Rahmawati Anwar, Desy; Luthfi, Mukhtar; Hamzah, M. Nasir (Program Pascasarjana, UIN Alauddin Makassar, 2022)
This research discusses the appropriateness between Maqasid Sharia aspects and the management of productive Waqf of Indonesian Muslim University's (UMI) Waqf Foundation. The primary objective of this research was to investigate whether the management practices of the Waqf of UMI had contributed to the dharuriyah needs of society or not. In this case, the Waqf management is expected to have beneficial functions for the religion and society where the distribution of its properties and returns could be used for the community's welfare. The methodological approach in this research was qualitative phenomenological, where the phenomena related to Maqasid Sharia and productive Waqf management at UMI foundation were investigated and thoroughly discussed. Last but not least, the Waqf development is carried out by actively providing the community with religious, Business, and health facilities. Therefore, based on the management practices mentioned above, the management of productive Waqf at the UMI foundation was considered to follow the principle of Maqasid Sharia. The purpose of Maqasih Sharia was to create prosperity and welfare for communities. This purpose has been considered to be achieved by the UMI foundation.